Discussion Panel: General Aviation Weather: Human Factors Issues and Current Research. (September 2017) - Ortiz, Yolanda; Blickensderfer, Beth; Johnson, Ian; Johnson, Chris; Caldwell, Barrett; Beringer, Dennis
Weather-related incidents account for the majority of general aviation accidents. Fortunately, a body of on-going, human factors research exists aimed at understanding and addressing this problem. The purpose of this session is to highlight that research. Topics will include the adequacy of pilots' aviation weather knowledge and skills, weather information presentation, and use of technology to assess pilot performance and to improve pilot training. The session is designed to lead a discussion about the complexity of aviation weather, the dangers of weather in GA flight and the research underway to minimize the hazards and improve air safety.